Technological advances in postharvest management of food grains - Hashim, Norhashila; I. Onwude, Daniel; Maringgal, Bernard (Academic Press, 2022)
Food grains such as cereals, legumes, and oilseeds are important food crops that contribute to most of the world’s staple food, especially in developing countries. However, up to ~   70% of food grains produced can be lost during postharvest management activities such as storage, transport, milling, drying, threshing, etc. The current challenge is to develop sustainable ways to reduce postharvest losses of food grains while increasing production. Several technological advancements have been made in recent years. In this chapter, the current state of the art of various advanced technologies used to reduce food grain losses during drying, milling, sorting, packaging, and storage is discussed. A future outlook to further develop these advances to drastically reduce the postharvest losses of food grains is also elucidated. Future research should be directed towards intensifying the use of smart sensors, IoT resources, and digital twins to enhance postharvest management practices. This book chapter provides valuable insight into sustainable technologies to improve postharvest management practices and reduce postharvest losses of food grains.